2009
DOI: 10.1007/s11244-009-9375-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into SO2 Interaction with Pd/Co3O4–CeO2 Catalysts for Methane Oxidation

Abstract: The catalytic performance and the sulphur resistance of a Pd (0.7 wt%) catalyst supported over Co 3 O 4 (30 wt%)-CeO 2 (70 wt%) mixed oxide were investigated in the oxidation of methane under stoichiometric and lean conditions. The catalytic behaviour was compared with that of two reference catalysts, palladium supported over pure Co 3 O 4 and CeO 2 . Catalysts were characterized by XRD, BET, XPS and FTIR measurements. Regeneration by a CH 4 -reducing treatment at 600°C was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 20 publications
4
49
0
1
Order By: Relevance
“…Figure 5 illustrates the experimental XPS spectra of the Co 2p3/2, O 1s, and S 2p regions for fresh Co1.0Ce and Co1.0Ce-S40h. The Co 2p3/2 peak binding energy (BE) for Co1.0Ce appeared at 781.2 eV, in agreement with the reference data [13,14,21]. There was no change in the BE for Co 2p3/2 of Co1.0Ce-S-40h, which was observed at 781.1 eV.…”
Section: Characterization Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…Figure 5 illustrates the experimental XPS spectra of the Co 2p3/2, O 1s, and S 2p regions for fresh Co1.0Ce and Co1.0Ce-S40h. The Co 2p3/2 peak binding energy (BE) for Co1.0Ce appeared at 781.2 eV, in agreement with the reference data [13,14,21]. There was no change in the BE for Co 2p3/2 of Co1.0Ce-S-40h, which was observed at 781.1 eV.…”
Section: Characterization Analysissupporting
confidence: 87%
“…A long exposure time to SO2 + O2 showed no effect on the electronic state of the cobalt according to the XPS results. Liotta et al [21] also found that the Co 2p spectrum did not change upon sulfur poisoning when they studied the SO2 effect on Pd/Co3O4 catalysts for CH4 oxidation. This suggested that Co3O4·SO3 was the dominant sulfate formed on Co3O4 [21].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 Recent works have demonstrated that the addition of ceria to cobaltic oxide allows cocatalyst production, with better performances with respect to pure Co 3 O 4 in terms of higher thermal stability and catalytic activity. [10][11][12][13][14][15] Ceria-based electrolytes are the most promising alternative to yttria-stabilized zirconia as a fast ionic conductor for solid oxide fuel cells, with the advantage of a lower operating temperature. [16][17][18] In recent years the increased interest in these materials has lead to many investigations aimed at studying efficient processes for the fabrication of ceria powders as well as to improve their sinterability.…”
mentioning
confidence: 99%
“…130 Outros estudos mostraram o potencial de catalisadores de platina suportados em óxidos mistos de cério e zircônio na reforma autotérmica do isooctano, na conversão de monóxido a dióxido de carbono a altas temperaturas e na remoção de óxidos de nitrogênio dos gases de exaustão automotivos.…”
unclassified